Original Research: A case-control genome-wide association study identifies genetic modifiers of fetal hemoglobin in sickle cell disease. Issue 7 (April 2016) - Liu, Li; Pertsemlidis, Alexander; Ding, Liang-Hao; Story, Michael D; Steinberg, Martin H; Sebastiani, Paola; Hoppe, Carolyn; Ballas, Samir K; Pace, Betty S
Sickle cell disease (SCD) is a group of inherited blood disorders that have in common a mutation in the sixth codon of the β-globin ( HBB ) gene on chromosome 11. However, people with the same genetic mutation display a wide range of clinical phenotypes. Fetal hemoglobin (HbF) expression is an important genetic modifier of SCD complications leading to milder symptoms and improved long-term survival. Therefore, we performed a genome-wide association study (GWAS) using a case-control experimental design in 244 African Americans with SCD to discover genetic factors associated with HbF expression. The case group consisted of subjects with HbF≥8.6% (133 samples) and control group subjects with HbF≤£ 3.1% (111 samples). Our GWAS results replicated SNPs previously identified in an erythroid-specific enhancer region located in the second intron of the BCL11A gene associated with HbF expression. In addition, we identified SNPs in the SPARC, GJC1, EFTUD2 and JAZF1 genes as novel candidates associated with HbF levels. To gain insights into mechanisms of globin gene regulation in the HBB locus, linkage disequilibrium (LD) and haplotype analyses were conducted. We observed strong LD in the low HbF group in contrast to a loss of LD and greater number of haplotypes in the high HbF group. A search of known HBB locus regulatory elements identified SNPs 5′ of δ-globin located in an HbF silencing region. In particular, SNP rs4910736 created a binding site for a known transcription repressor GFi1 which is a candidate protein for further investigation. Another HbF-associated SNP, rs2855122 in the cAMP response element upstream of Gγ-globin, was analyzed for functional relevance. Studies performed with siRNA-mediated CREB binding protein (CBP) knockdown in primary erythroid cells demonstrated γ-globin activation and HbF induction, supporting a repressor role for CBP. This study identifies possible molecular determinants of HbF production.